The Strategy of the Environment and Hygiene Office in Overcoming the Existence of Illegal Temporary Shelter (TPS) in Pekanbaru - Nini Astuti; Irawaty Irawaty; Fara Merian Sari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
This paper discusses the strategies by Environment and Hygiene Office (DLHK) in overcoming the existence of illegal temporary shelter (TPS) in Pekanbaru. The theory used is the Hatten and Hatten which suggests what the principles in the success of a strategy are. While this is qualitative research with a descriptive design, the results show that Environment and Hygiene Office's strategy for combating the presence of illegal temporary shelter is adequate. However, due to the lack of public awareness to comply with the regulations set by the office, it was difficult for them to solve the problem of illegal temporary shelter in Pekanbaru.